2017
DOI: 10.1248/yakushi.16-00233-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Preparation of Ephedrine Alkaloids-free Ephedra Herb Extract and Its Antitumor Effect and Putative Marker Compound

Abstract: Ephedra Herb is a crude drug for the treatment of headache, bronchial asthma, nasal in‰ammation, and the common cold. Although it has been considered that ephedrine alkaloids (EAs) are the principal active ingredients of Ephedra Herb, EAs are known to induce palpitations, hypertension, insomnia, and dysuria as major side eŠects. Therefore, the administration of EAs-containing drugs to patients with cardiovascular-related diseases is strongly contraindicated. Previously, we isolated herbacetin 7-O-neohesperidos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Ephedra aphylla has been reported as being rich with valuable phytochemicals such as alkaloids like ephedrine, pseudoephedrine, N-methylephedrine, and 6-methoxykynurenic acid, and hordenine [22,23], phenolics and flavonoids, i.e., di-C-glucosyl flavone, 2,2di-O-β-glucopyranosyl-vicenin, di-O-glycoside, herbacetin 3-O-α -rhamnopyranoside-8-O-β-glucopyranoside, vicenin, 7-methoxy-4-oxo-1,4-dihydroquinoline-2-carboxylic acid, ephedralone, 4-hydroxybenzoic acid, (E)-3-(4-hydroxyphenyl)acrylic acid, 3,4-dihydroxybenzoic acid, and 7-methoxy-herbacetin [24,25]. Some of the phytochemical constituents in Ephedra aphylla possess larvicidal activity and could be used for controlling disease-caused by mosquitoes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Ephedra aphylla has been reported as being rich with valuable phytochemicals such as alkaloids like ephedrine, pseudoephedrine, N-methylephedrine, and 6-methoxykynurenic acid, and hordenine [22,23], phenolics and flavonoids, i.e., di-C-glucosyl flavone, 2,2di-O-β-glucopyranosyl-vicenin, di-O-glycoside, herbacetin 3-O-α -rhamnopyranoside-8-O-β-glucopyranoside, vicenin, 7-methoxy-4-oxo-1,4-dihydroquinoline-2-carboxylic acid, ephedralone, 4-hydroxybenzoic acid, (E)-3-(4-hydroxyphenyl)acrylic acid, 3,4-dihydroxybenzoic acid, and 7-methoxy-herbacetin [24,25]. Some of the phytochemical constituents in Ephedra aphylla possess larvicidal activity and could be used for controlling disease-caused by mosquitoes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Although Ephedra is suitable for treating sweating and fever, it is also commonly used for pain relief in clinics. A study reported that a flavonoid aglycone present in herbacetin 7- O -neohsperidin in Ephedra has anticancer cell proliferation effects and analgesic properties [ 102 ]. It could also inhibit the abnormal proliferation of cancer cells induced by the hepatocyte growth factor (HGF) by inhibiting C-Met phosphorylation and its tyrosine kinase activity through the PI3K/Akt pathway [ 103 , 104 ].…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…EH has been used for medicinal purposes for thousands of years with its biological and pharmacological properties, such as antioxidative, antimicrobial, antiinflammatory, antiallergic, and antiproliferative effects [11][12][13]. Recently, it is widely used to treat bronchial asthma, cardiovascular related diseases, immune system diseases, cancer, and other diseases [14][15][16]. Moreover, it is reported that EH has positive effects on the treatment of NS through reducing protein in the urine, alleviating kidney functional and structural impairment [17,18].…”
Section: Introductionmentioning
confidence: 99%